New Zealand’s Ombudsmen Legislation: The Need for Amendments After Almost 50 Years - Chen, Mai (Victoria University of Wellington Law Review, 2010)
It has been almost fifty years since the original Parliamentary Commissioner (Ombudsman) Act was passed in 1962, the precursor to the current Ombudsmen Act 1975. Since that time, the role has expanded significantly and the constitutional framework in which the Ombudsman operates has also changed significantly, yet the legislation has never undergone a thorough review. In this article, Mai Chen examines how Ombudsmen are a key tool in the Public Law Toolbox. She reviews the functions of the Office, showing that it can be more effective than courts in addressing issues of public administration in some circumstances, due to its accessibility, low cost to the complainant, and range of remedies available. The article concludes that as so much of the Ombudsmen’s work is in private, the lack of formal use of statutory powers to compel or to make formal recommendations may actually evidence their effectiveness in using persuasion to get those complained about to redress the problem. Ms Chen makes a number of reform proposals to reflect recent developments, and to allow the Office to fulfil its constitutional role including a specific public education function, a 20 working day deadline on providing the Ombudsmen with any information requested, a presumption of jurisdiction for bodies exercising public powers affecting the public and which are publicly funded, an express power to comment on law-making with implications for the Ombudsmen and Official Information Acts, extending jurisdiction to "committees of the whole" in Local Government, and a single fixed term to protect Ombudsmen independence in office. The article also considers whether wide use of the name Ombudsmen should be allowed for private sector investigative and complaints bodies.